2021
DOI: 10.1111/dom.14519
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamic bioequivalence of biosimilar MYL‐1601D with US and European insulin aspart in healthy volunteers: A randomized, double‐blind, crossover, euglycaemic glucose clamp study

Abstract: Aim: To evaluate the pharmacokinetic (PK) and pharmacodynamic (PD) bioequivalence (BE) of MYL-1601D biosimilar with originator, NovoLog (Ref-InsAsp-US), and NovoRapid (Ref-InsAsp-EU).Materials and Methods: This was a double-blind, randomized, crossover study that enrolled 71 healthy subjects to receive a single subcutaneous dose (0.2 U/kg) of each formulation under automated euglycaemic clamp conditions (ClampArt, level 81 mg/dL, duration 12 hours postdose). Primary PK endpoints were area under the plasma insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The analytical comparison showed that MYL-1601D and reference product are highly similar molecules with respect to physicochemical and functional properties [ 9 ]. The current study was designed to address the residual uncertainty and to detect differences between the treatments groups with immunogenicity parameters [ 27 ] as the primary endpoint following demonstration of PK-PD similarity in a euglycemic clamp study, which was more sensitive to detect any difference between the biosimilar and reference product compared with HbA1C in the diabetes patients [ 10 ]. Further, the study design, including primary and secondary endpoints, population selection, treatment duration, proposed margins, and statistical assumptions, was in accordance with the US-FDA scientific advice to ensure robust patient exposure to detect differences in immunogenicity, efficacy, and safety parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analytical comparison showed that MYL-1601D and reference product are highly similar molecules with respect to physicochemical and functional properties [ 9 ]. The current study was designed to address the residual uncertainty and to detect differences between the treatments groups with immunogenicity parameters [ 27 ] as the primary endpoint following demonstration of PK-PD similarity in a euglycemic clamp study, which was more sensitive to detect any difference between the biosimilar and reference product compared with HbA1C in the diabetes patients [ 10 ]. Further, the study design, including primary and secondary endpoints, population selection, treatment duration, proposed margins, and statistical assumptions, was in accordance with the US-FDA scientific advice to ensure robust patient exposure to detect differences in immunogenicity, efficacy, and safety parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative and quantitative composition of MYL-1601D has been identical to that of Ref-InsAsp-US and Ref-InsAsp-EU in physicochemical analyses and nonclinical studies with no clinically meaningful differences observed [ 9 ]. A euglycemic clamp study demonstrated pharmacokinetic (PK) and pharmacodynamic (PD) similarity of MYL-1601D versus both Ref-InsAsp-US and Ref-InsAsp-EU in healthy volunteers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%